PELAKSANAAN PEMENUHAN KEWAJIBAN PAJAK PENGHASILAN PASAL 23 OLEH PT PARANI ARTAMANDIRI - Endro Andayani; Tavitri Rangkuti; Rahmat Ramdhani Fitrah (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2015)
The biggest state revenue is from the tax sector, various ways are done to optimize the revenue. One of them is the Withholding tax system. Article 23 Income Tax is one type of tax that applies this system. With the tax object on income from dividends, royalties, interest, rents other than land and building leases, prizes and awards as well as other service benefits in accordance with the Minister of Finance Regulation. Whereas one of the tax subjects is the State Dalan tax payer. PT Parani Artamandiri as a Domestic Taxpayer is obliged to carry out Calculations, Deductions, Deposits and Reporting on Debt Tax Article 23. In carrying out the fulfillment of these obligations, PT Parani Artamandiri experienced obstacles in the implementation of deposits. this is because the company is experiencing bad cashflow. The purpose of this study is to determine the implementation of the fulfillment of Article 23 Income Tax obligations by PT Parani Artamandiri Jakarta in 2015 whether it is in accordance with the applicable tax regulations. In collecting data the author observes and quotes documents. It was concluded in the implementation of the fulfillment of Article 23 Income Tax obligations by PT Parani Artamandiri Jakarta in 2015 not in accordance with the applicable tax regulations